Field notes contributed by Babs Padelford and Loren Padelford, fall 1991 - Padelford, Babset al; Padelford, Lorenet al (1991)
List of birds and locations contributed by Babs Padelford and Loren Padelford with observers Alan G. Grenon, Jerry Toll, Tanya Bray and Mike Brown. The field notes include a separate list for November bird sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed